2009
DOI: 10.1159/000209741
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preceding Inspiratory Speed and End-Inspiratory Pause on Forced Expiratory Manoeuvre in Healthy Subjects and Chronic Obstructive Pulmonary Disease Patients

Abstract: Background: Lower peak expiratory flow (PEF) and forced expiratory volume in 1 s (FEV1) have been consistently found after slow inspiration with end-inspiratory pause (EIP). Objectives: It was the aim of this study to establish the respective influence of the speed of preceding inspiration (SPI) and EIP on the parameters obtained from the following expiratory forced vital capacity (FVC) manoeuvre. Methods: In 8 healthy subjects and 12 patients with chronic obstructive pulmonary disease (COPD), a num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Boni et al studied the effect of the preceding inspiratory speed and the end-inspiratory pause in a forced expiratory maneuver with healthy subjects and COPD patients and found that the speed of the preceding inspiration did not influence the subsequent expiratory-flow peak or the FEV 1 in either healthy subjects or COPD patients, unless the former became >2 s. By contrast, any end-inspiratory pause decreased these indices in all individuals [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Boni et al studied the effect of the preceding inspiratory speed and the end-inspiratory pause in a forced expiratory maneuver with healthy subjects and COPD patients and found that the speed of the preceding inspiration did not influence the subsequent expiratory-flow peak or the FEV 1 in either healthy subjects or COPD patients, unless the former became >2 s. By contrast, any end-inspiratory pause decreased these indices in all individuals [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the slow inspiration method resulted in a lower elastic recoil pressure, a trend that may differ from that of normal and RPD. Boni et al [ 25 ] investigated the effects of preceding inspiratory velocity and respiratory pauses on a forced expiratory maneuver in healthy subjects and patients with COPD. They reported that unless the receding inspiratory velocity was longer than 2 seconds, it did not affect PEF and FEV1 in either healthy subjects or patients with COPD.…”
Section: Discussionmentioning
confidence: 99%